In vitro cytotoxicity of cabazitaxel in adrenocortical carcinoma cell lines and human adrenocortical carcinoma primary cell cultures☆. (1st December 2019) - Fragni, Martina; Palma Lopez, Lilian Patricia; Rossini, Elisa; Abate, Andrea; Cosentini, Deborah; Salvi, Valentina; Vezzoli, Sara; Poliani, Pietro Luigi; Bosisio, Daniela; Hantel, Constanze; Tiberio, Guido A.M.; Grisanti, Salvatore; et al.
Abstract: Adrenocortical cancer (ACC) is a rare and aggressive malignancy with a poor prognosis. The overall 5-year survival rate of patients with ENS@T stage IV ACC is less than 15%. Systemic antineoplastic therapies have a limited efficacy and new drugs are urgently needed. Human ACC primary cultures and cell lines were used to assess the cytotoxic effect of cabazitaxel, and the role of P-glycoprotein in mediating this effect. Cabazitaxel reduced ACC cell viability, both in ACC cell lines and in ACC primary cell cultures. Molecular and pharmacological targeting of ABCB1/P-gp did not modify its cytotoxic effect in NCI–H295R cells, while it increased the paclitaxel-induced toxicity. Cabazitaxel modified the expression of proteins involved in cellular physiology, such as apoptosis and cell cycle regulation. The drug combination cabazitaxel/mitotane exerted an additive/moderate synergism in different ACC cell experimental models. These results provide a rationale for testing cabazitaxel in a clinical study. Highlights: Cabazitaxel was cytotoxic in ACC primary cell cultures and in ACC cell lines. Cabazitaxel effect was insensitive to P-gp expression. Combination treatment of cabazitaxel and mitotane exerted a synergic cytotoxicity. Cabazitaxel activated both the extrinsic and intrinsic apoptosis in NCI–H295R cells.